Croatia and NATO - Tatalović Siniša (Međunarodni Problemi)
The purpose of this article is to study the relations between the Republic of Croatia and NATO. The paper analyses the process of Croatia’s approaching to NATO. By adopting the new strategic concept of NATO at the 1999 Washington summit and conclusions at the 2002 Prague summit the Alliance has confirmed its willingness to enlarge itself through the Partnership for Peace programme. This programme has established itself as a bridge for inclusion of NATO non-member countries into its activities by achieving their interoperability with the Alliance. By all this, the Partnership for Peace has become one of the tools for encouraging defence and security co-operation among European countries, regardless of the fact whether they are NATO members or not. Such a position of NATO in the European security architecture and its enlargement by admitting new member states is of special significance for the Croatian activities taken and directed towards this organisation. Through its activities within the Partnership for Peace Croatia makes preparations to achieve interoperability with NATO. These activities constitute a part of the preparations for its future membership in the Alliance (this also includes the reform of the security and defence system). On the other hand, the co-operation with NATO (together with other mechanisms such as OSCE and the Stability Pact) enables Croatia to exerts its influence towards stabilisation of the situation in this part of South-Eastern Europe, achieving at the same time its key political, economic and security interests in the region.